2019
DOI: 10.1101/688861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reducing expression of dynamin-related protein 1 increases radiation sensitivity of glioblastoma cells

Abstract: 172 words Cheng, 2 -Text: 16 pages, 3732 words Figures, 5 Tables, 1 Cheng, 3 - Translational RelevanceThis study shows that dynamin-related protein 1 (DRP1), an essential 80-kDa GTPase, which is involved in mitochondrial fission, and mitochondrial protein imports, is highly expressed in glioblastoma multiforme (GBM). Moreover, we demonstrate that DRP1 expression is closely associated with radiation sensitivity, cancer progression, and patients' cumulative survival. In vitro, inhibition of DRP1 expression reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…These reports indicate that Drp1 mediates cell death. Conversely, the protective effects of Drp1 on cell death have also been reported [ 33 , 34 , 35 ]. For example, depletion of Drp1 is known to increase apoptosis in human colon cancer cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports indicate that Drp1 mediates cell death. Conversely, the protective effects of Drp1 on cell death have also been reported [ 33 , 34 , 35 ]. For example, depletion of Drp1 is known to increase apoptosis in human colon cancer cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, depletion of Drp1 is known to increase apoptosis in human colon cancer cells [ 33 ]. In addition, Chen et al reported that silencing of Drp1 increased radiosensitivity of UM87MG and T98G human glioblastoma cells [ 34 ]. Furthermore, Akita et al demonstrated that Drp1-knockdown sensitized A375 cells (a human malignant melanoma) and A549 to tumor necrosis factor-related apoptosis-inducing ligand, although Drp1-knockdown by itself did not increase the rate of apoptosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, neither acute nor chronic morphine treatment appears to influence DRP1 expression in nonneural GBM cell lines; however, previous studies suggest that the DRP1 pathway participates actively in facilitating migration and invasion of GBM cells, highlighting its role in proliferation and spread of GBM 66 . Strategies to decrease DRP1 expression could obstruct DNA repair mechanisms while heightening the radiosensitivity of GBM cells 67 . Nevertheless, there exists a noticeable gap in the research regarding this issue.…”
Section: Discussionmentioning
confidence: 98%
“…66 Strategies to decrease DRP1 expression could obstruct DNA repair mechanisms while heightening the radiosensitivity of GBM cells. 67 Nevertheless, there exists a noticeable gap in the research regarding this issue. The proposed combined treatment offers an opportunity for future studies on pain management in patients with GBM.…”
Section: Exploring New Treatment Avenues: Focus On Cabergolinementioning
confidence: 99%